The global impact of adverse childhood experiences on criminal behavior: A cross-continental study - Basto-Pereira, Miguel (2022)
Background: Adverse Childhood Experiences (ACEs) have been associated with a greater risk of later criminal offending. However, existing research in this area has been primarily conducted in Western developed countries and cross-cultural studies are rare. Objectives: This study examined the relationship between ACEs and criminal behaviors in young adults living in 10 countries located across five continents, after accounting for sex, age, and cross-national differences. Participants and setting: In total, 3797 young adults aged between 18 and 20 years (M = 18.97; DP = 0.81) were assessed locally in community settings within the 10 countries.Method: The ACE Questionnaire was used to assess maltreatment and household dysfunction during childhood and a subset of questions derived from the Deviant Behavior Variety Scale (DBVS) was used to determine past-year criminal variety pertaining to 10 acts considered crime across participating countries. Results: Physical and sexual abuse, physical neglect, and household substance abuse were related to criminal variety, globally, and independently across sexes and countries ranked differently in the United Nations Human Development Index (HDI). In addition, three out of five experiences of household dysfunction were related to criminal variety, but subsequent analyses indicate that some forms of household dysfunction only hold statistical significance among males or females, or in countries ranking lower in the HDI. Conclusions: This research strengthens the finding that there are cross-cultural mechanisms perpetuating the cycle of violence. It also indicates that forms of household dysfunction have an impact on criminal behavior that is shaped by gender and the country's levels of social well-being.